Moxifloxacin Treatment for Contact Lens-Related Corneal Ulcer: A Case Report: Poster Presentation - Case Report - General practitioner - Gek Ayu Krismayogi; AA Sagung Mirah Prabandari; Harumi Purwa Prahesthy (Majalah Oftalmologi Indonesia, 2023)
Introduction : A corneal ulcer is an ophthalmological emergency that can threaten vision. It is characterized by inflammation or infection involving the corneal epithelium and stroma. Prolonged use of contact lenses is more likely to cause corneal ulcers. The purpose of this paper is to report on the management of corneal ulcers. Case Illustration : A 30-year-old female complained of blurred vision, redness, pain, swelling, and sensitivity to light in both eyes for the last two days. She reported falling asleep in her contact lenses two nights before the visit. The patient had compound myopic astigmatism before and her visual acuity was decreased to 3/60 in the right eye and 5/60 in the left eye, examinations showed palpebral edema and conjunctival hyperemia in both eyes. The use of fluorescein in both eyes highlighted the area of the defect. The patient was diagnosed with corneal ulcers. Treatments were Moxifloxacin Eye Drop every hour and Ibuprofen 2x400 mg by intravenous infusion. On the last visit, the corneas were clear with visual acuity 6/15 in both eyes. Discussion : According to the study by Kishor et al., ophthalmic eye drop is the most effective treatment and fourth-generation fluoroquinolones represent the most frequently used strategies in Corneal Ulcer.Conclusion : Antibiotics and analgesics are effective for the management of corneal ulcers in this patient. Education regarding contact lenses is important to prevent the occurrence of corneal ulcers.